2015 Guidance on cancer immunotherapy development in early‐phase clinical studies. Issue 12 (December 2015) - ,; ,; ,; ,; ,; ,; ,
Abstract : The development of cancer immunotherapies is progressing rapidly with a variety of technological approaches. They consist of "cancer vaccines", which are based on the idea of vaccination, "effector cell therapy", classified as passive immunotherapy, and "inhibition of immunosuppression", which intends to break immunological tolerance to autoantigens or immunosuppressive environments characterizing antitumor immune responses. Recent reports showing clinical evidence of efficacy of immune checkpoint inhibitors and adoptive immunotherapies with tumor‐infiltrating lymphocytes and tumor‐specific receptor gene‐modified T cells indicate the beginning of a new era for cancer immunotherapy. This guidance summarizes ideas that will be helpful to those who plan to develop cancer immunotherapy. The aims of this guidance are to discuss and offer important points in early phase clinical studies of innovative cancer immunotherapy, with future progress in this field, and to contribute to the effective development of cancer immunotherapy aligned with the scope of regulatory science. This guidance covers cancer vaccines, effector cell therapy, and inhibition of immunosuppression, including immune checkpoint inhibitors.